Antimicrobial Resistance Profile, Whole-Genome Sequencing and Core Genome Multilocus Sequence Typing of B. anthracis Isolates in Croatia from 2001 to 2022 - Gordan Kompes; Sanja Duvnjak; Irena Reil; Željko Mihaljević; Boris Habrun; Miroslav Benić; Luka Cvetnić; Silvio Špičić; Antonela Bagarić (MDPI AG, 2024)
Bacillus anthracis, the causative agent of anthrax disease, is a worldwide threat to livestock, wildlife and public health. It is also considered one of the most important pathogens of bioterrorism. Rapid and reliable diagnosis and administration of antimicrobials are essential for effective anthrax treatment. In this study, we determined the in vitro susceptibilities of 40 isolates of B. anthracis isolated in Croatia over the recent two decades to 18 antimicrobials. Whole-genome sequencing was performed, and bioinformatics tools were used to determine virulence factors and antimicrobial resistance genes. Core genome-based multilocus sequence typing was used for isolate comparison and phylogenetic analysis. All isolates were susceptible to all antimicrobials recommended for post-exposure prophylaxis or anthrax therapy. Susceptibility was found to all other tested antimicrobials that are an alternative for primary therapy. We found two beta-lactamase genes, but their expression is not sufficient to confer resistance. In all isolates used in this study, we found 21 virulence genes, 8 of which are responsible for toxin and capsule production. As far as phylogenetic analysis is concerned, the B. anthracis isolates from Croatia are categorised into two clades. The first is clade A, subclade Trans Eurasia, and the other is clade B, subclade B2.